KEMAMPUAN BERPIKIR KRITIS MAHASISWA MANAJEMEN UMSIDA DALAM MEMECAHKAN MASALAH MATEMATIKA BISNIS - Bayu Hari Prasojo; Novia Ariyanti (Universitas PGRI Adi Buana Surabaya, 2017)
This descriptive study used a quantitative approach that aims at describing the students' critical thinking in solving business mathematics problems with respect to the origin of the school majors. Subjects were students of FEB management UMSIDA first half of the academic year 2016/2017. Data collection techniques in the form of tests to complete the Problem Solving Test (TPM) and the provision of critical thinking questionnaire relating to the work of students on TPM has been given. Data were analyzed using the average, percentage and Pearson Product Moment Correlation test (PPM). And the results showed that (1) the ability to solve business mathematics problems, student majoring in science studies is higher than the ability to solve mathematical problems business student majoring in social studies or student majoring in vocational school (2) critical thinking skills of students majoring in science studies, social studies and vocational school overall thinking ability critical successively shows the critical criterion, quite critical and critical enough (3) critical thinking skills of students at every step of Polya’s Problem Solving as follows: (a) at the stage Understanding the problem, a student of the science studies showed criteria please critical, a student of the social studies indicate criteria quite Critical and student of vocational school indicate the criteria fairly Critical (b) at the stage Make a Plan, a student of the science studies indicates the criteria fairly critical, a student of the social studies indicate criteria is quite critical and student of vocational school indicate the criteria fairly Critical (c) at the stage implement the plan, a student of the science studies showed criteria please Critical, a student of the social studies indicate criteria please Critical and student of vocational school indicate criteria please Critical (c) at the stage Checking Back, a student of the science studies indicates the criteria Critical, a student of the social studies show Critical criteria and student of vocational schools show the criteria, please Critical (4) there is a strong relationship between Business Mathematics problem Solving ability with Students Critical Thinking Skills. Keywords: evaluation of learning, realibility, discrimination power